2018
DOI: 10.1007/s10461-018-2151-0
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Relationships in PrEP Uptake and Use Among Transgender Women and Men Who Have Sex with Men

Abstract: Qualitative studies suggest that social relationships play an important role in HIV pre-exposure prophylaxis (PrEP) use, but there have been few quantitative assessments of the role of social relationships in PrEP uptake or adherence. We examined the association between disclosure of study participation or LGBT identity and PrEP use in the 1603 HIV-negative participants enrolled in the iPrEx OLE study. We also evaluated the association between LGBT social group involvement and PrEP use. Study participation dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 29 publications
3
26
0
Order By: Relevance
“…Particularly at a time when PrEP is not yet formally available, men in social networks that included PrEP users appeared to have greater access to information about how to obtain PrEP. These results echo prior findings that social networks play a central role in PrEP contemplation and adoption among transgender women and MSM 34 and among gay and bisexual men 35 and suggest the potential of utilizing social networks to increase PrEP contemplation and uptake in China. 36 In our sample, we found that medical providers were cited as the least common source of PrEP information.…”
Section: Discussionsupporting
confidence: 84%
“…Particularly at a time when PrEP is not yet formally available, men in social networks that included PrEP users appeared to have greater access to information about how to obtain PrEP. These results echo prior findings that social networks play a central role in PrEP contemplation and adoption among transgender women and MSM 34 and among gay and bisexual men 35 and suggest the potential of utilizing social networks to increase PrEP contemplation and uptake in China. 36 In our sample, we found that medical providers were cited as the least common source of PrEP information.…”
Section: Discussionsupporting
confidence: 84%
“…Social support within the trans community may help lessen the effects of PrEP stigma much in the same way that it has done with other forms of stigma. 1,37,38 Social support in the context of PrEP use may also help facilitate PrEP uptake and persistence among highly marginalized BLTW. 37…”
Section: Discussionmentioning
confidence: 99%
“…These findings add to the burgeoning literature on social networks and PrEP, which has primarily focused on men. [13][14][15]22,23 These findings also have important implications for the development and implementation of social network-based approaches to HIV prevention for women, particularly women experiencing IPV.…”
Section: Discussionmentioning
confidence: 85%
“…In addition to abusive partners, some PrEP research found that family and friends could have positive and/or negative influences on PrEP adherence. 12,13 Women experiencing IPV may face additional difficulties accessing PrEP and less support from their social network, however, no study has examined IPV as an effect modifier on the association between women's social networks and the PrEP care continuum. A growing number of PrEP engagement interventions are leveraging social networks among men who have sex with men, 14,15 but this intervention delivery format may only enhance PrEP engagement among those with supportive social networks.…”
Section: Introductionmentioning
confidence: 99%